TINDAK TUTUR PENOLAKAN CINTA DALAM DRAMA 5 JI KARA 9 JI MADE - Ilyas, Reymona; Isnaini, Zuli Laili; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to describe the refusal speech act of love, the current situation and the politeness when the refusal speech act of love happened. The subject of this research is 5 Ji Kara 9 Ji Made drama created by Miki Aihara in 2015. This is a descriptive research with a qualitative approach that use SPEAKING theory from Dell Hymes. After that, it is connected by politeness principle theory by Lecch, the face threatening theory and the politeness strategies by Brown and Levinson. In the result, we discovered that there were some kinds of the refusal of love with various levels of politeness were used. The violation of politeness principle, the maxims in the face threatening act and politeness strategies that done had relevance to the situation happened when the speech event. There were two kinds of refusal speech act of love in the 5 Ji Kara 9 Ji Made drama. They were the reason of refusal the love and the request that are not approachable.Keywords: The refusal speech act of love, politeness, facethreatening acts, politeness strategies